Treatment of palm oil mill secondary effluent (POMSE) using fenton oxidation system - Ooi, Boon Siew (2006)
The feasibility of Fenton oxidation system to treat palm oil mill secondary effluent (POMSE) was investigated in this study. This study also evaluated the effect of UV lamp and solar light on the efficiency of Fenton oxidation in term of COD, colour and organic content removal within the experimental design. The Fenton oxidation processes were optimized by applying Central Composite Rotatable Design (CCRD). While the results depend on the concentration of reagents used in the study, in general, COD (82.4%) and UV absorbance (86.1%) were best removed using Solar-Fenton reagent. Colour (95.5%) was best removed using Photo-Fenton reagent. The best overall removal in term of COD (82.4%), colour (92.1%) and UV absorbance (83.3%) was achieved using Solar-Fenton reagent with 348.7 mg/L Fe2+ and 1397.5 mg/L H2O2. Using factorial analysis, p-value in Fenton reagent indicated the significance of iron dosage and significance of interaction effect between two variables (Fe2+ and H2O2) on COD and colour removal. It was found that only iron dosage gave significant effect to the COD, colour and UV removal in Photo-Fenton study. In Solar-Fenton study, iron dosage, H2O2 dosage and interaction effect between the two variables (Fe2+ and H2O2) were significant on COD removal. However, only iron dosage gave significant effect on colour and UV removal in Solar-Fenton study. Statistical relationship between COD and UV absorbance removal with Fe2+, H2O2 dosage was also developed in this study